1995
DOI: 10.1243/pime_proc_1995_209_349_02
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Contact Mechanics of Five Total Knee Joint Replacements

Abstract: The tibio-femoral contact area in five current popular total knee joint replacements has been measured using pressure-sensitive film under a normal load of 2.5 kN and at several angles of flexion. The corresponding maximum contact pressure has been estimated from the measured contact areas and found to exceed the point at which plastic deformation is expected in the ultra-high molecular weight polyethylene (UHMWPE) component, particularly at flexion angles near 90 degrees. The measured contact area and the est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…The extent of delamination is affected by various factors including high contact stress and low congruity (Walker, 1988;Bartel et al, 1986). Experimental (Stewart et al, 1995) and theoretical (Jin et al, 1995a, b) studies have shown that as geometries become less conforming the values of peak contact stress approach and exceed the yield stress of UHMWPE making it more prone to fatigue failure.…”
Section: Introductionmentioning
confidence: 99%
“…The extent of delamination is affected by various factors including high contact stress and low congruity (Walker, 1988;Bartel et al, 1986). Experimental (Stewart et al, 1995) and theoretical (Jin et al, 1995a, b) studies have shown that as geometries become less conforming the values of peak contact stress approach and exceed the yield stress of UHMWPE making it more prone to fatigue failure.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in total knee replacement (TKR) designs, materials and sterilisation techniques during the past decade have led to improved clinical performance of these prostheses by reducing the prevalence of delamination and structural fatigue of the ultra high molecular weight polyethylene (UHMWPE) bearings (Stewart et al, 1995;Won et al, 2000;Reeves et al, 2000;Bell et al, 1998). However, in the longer term, concern remains regarding the surface wear of total knee components as the generation and accumulation of micrometre and submicrometre size wear particles has been observed in tissues surrounding knee replacements which were revised for infection in the early years of implantation (Howling et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that the boundary conditions (including loading) applied to the third-body wear particle (micro-model ) were determined from the contact between the two articulating surfaces (macro-model ). The contact pressure between the two articulating surfaces, which has been reported for both hip and knee implants employing UHMWPE components in previous studies [19][20][21], was used as an input condition to the present micro-model. Figure 1b shows the local set-up of the micro-model from which a simple twodimensional axisymmetric nite element model (as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%